Room-temperature enantioselective C–H iodination via kinetic resolution - Chu, Ling; Xiao, Kai-Jiong; Yu, Jin-Quan (Science (American Association for the Advancement of Science), 2014)
Asymmetric carbon-hydrogen (C–H) activation reactions often rely on desymmetrization of prochiral C–H bonds on the same achiral molecule, using a chiral catalyst. Here, we report a kinetic resolution via palladium-catalyzed enantioselective C–H iodination in which one of the enantiomers of a racemic benzylic amine substrates undergoes faster aryl C–H insertion with the chiral catalysts than the other. The resulting enantioenriched C–H functionalization products would not be accessible through desymmetrization of prochiral C–H bonds. The exceedingly high relative rate ratio (k fast/k slow up to 244), coupled with the subsequent iodination of the remaining enantiomerically enriched starting material using a chiral ligand with the opposite configuration, enables conversion of both substrate enantiomers into enantiomerically pure iodinated products.